(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Putra B, Warly L, Evitayani, Utama BP. 2021. The role of arbuscular mycorrhizal fungi in phytoremediation of heavy metals and their effect on the growth of Pennisetum purpureum cv. Mott on gold mine tailings in Muara Bungo, Jambi, Indonesia. Biodiversitas 23: 478-485. The increase of heavy metal pollution in the soil results from human activities such as gold mining, which impacts human and environmental health problems. Phytoremediation is an environmentally friendly, inexpensive, and efficient solution to overcome environmental damage caused by heavy metal contamination. Inoculation of AMF in dwarf Napier grass can reduce the level of metal contaminants in soil and subsequently its absorption in plant tissue. This study investigates the effect of arbuscular mycorrhizal fungi (AMF) on dwarf Napier grass (Pennisetum purpureum cv. Mott) plant growth and heavy metal remediation rates. The experiment was a completely randomized design with 4 levels of AMF inoculation (0, 5, 10, and 15 g/pot) with 5 repetitions. After eight weeks of potting experiments, shoot and root biomass, plant growth, heavy metal content in potting media were assessed. The results revealed that AMF inoculation of 10 g/pot exhibited a higher growth yield of dwarf Napier grass compared to other treatments (plant height (p<0.01), leaf length (P<0.01), leaf width (P<0.01), stem diameter (P<0.01) and plant fresh weight (P<0.01)), but had no significant effect on the number of leaves and number of shoots (P>0.05). AMF (10 g/pot) significantly affected root growth of dwarf Napier grass (root length (P<0.01), number of roots (P<0.05), and root fresh weight (P<0.01)). The results also showed that AMF increased the uptake of Al, Co, Cr, and Fe significantly in the growing media (Al (P<0.01), Co (P<0.05), Cr (P<0.01), Fe (P<0.05) but no significant effect on Pb (P>0.05). This study concluded that AMF effectively increased the growth of dwarf Napier grass and reduced heavy metal contaminants on gold mines tailings.